Analysis of the Relationship Between MedRiPh (Medication Risk in Pharmacotherapy) Scores and the Incidence of Drug-Related Problems (DRPs) in Geriatric Patients with Comorbidities at Community Health Center X, Surabaya - Rissa Maharani Dewi; Lilik Septiana; Diki Aprianto A; Ratna mildawati; Eka Nur Fatmawati (Fundamental and Applied Research in Medicine and Allied Sciences Indonesia, 2025)
Drug-Related Problems (DRPs) remain a significant issue in geriatric pharmacotherapy, particularly among older adults with multiple chronic conditions and complex medication regimens. The MedRiPh (Medication Risk in Pharmacotherapy) scoring model has been introduced to identify patients at higher risk of medication related harm, yet its usefulness in Indonesian primary care has not been well evaluated. This cross-sectional study was conducted from October to December 2024 involving 100 geriatric patients aged ≥60 years selected using purposive sampling. MedRiPh scores were calculated using validated criteria, and DRPs were identified based on the Pharmaceutical Care Network Europe (PCNE) version 9.1 system. Statistical analysis included the Shapiro Wilk test, Spearman correlation, and linear regression. A total of 412 DRPs were recorded, with drug interactions, dosing errors, and duplicate therapies being the most common. A strong correlation was found between MedRiPh scores and DRPs (r = 0.82, p < 0.001). These results indicate that MedRiPh may be useful for improving medication safety in geriatric primary care.